2022
DOI: 10.1007/s11031-022-09937-2
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen disgust sensitivity: Individual differences in pathogen perception or pathogen avoidance?

Abstract: The emotion disgust motivates the avoidance of pathogens and contaminants. Individuals differ in their tendency to experience disgust and this is referred to as pathogen disgust sensitivity. Yet, it remains unclear which differences in psychological processes are captured by pathogen disgust sensitivity. We tested two hypotheses about how the information processing structure underlying pathogen avoidance might give rise to individual differences in pathogen disgust sensitivity. Participants (n = 998) rated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…However, results were in alignment with several studies in the behavioral immune system literature, including the negative correlation between contact comfort and pathogen disgust sensitivity reported by and van Leeuwen & Jaeger (2022). Furthermore, our findings showed a decrease in contact comfort for faces manipulated as infectious compared to faces without manipulation, as previously reported by van…”
Section: Comfort Of Contact With Outgroupssupporting
confidence: 93%
See 1 more Smart Citation
“…However, results were in alignment with several studies in the behavioral immune system literature, including the negative correlation between contact comfort and pathogen disgust sensitivity reported by and van Leeuwen & Jaeger (2022). Furthermore, our findings showed a decrease in contact comfort for faces manipulated as infectious compared to faces without manipulation, as previously reported by van…”
Section: Comfort Of Contact With Outgroupssupporting
confidence: 93%
“…Nevertheless, many of our other findings were consistent with those from previous studies in the behavioral immune system literature. For example, contact comfort was negatively related to pathogen disgust sensitivity Leeuwen & Jaeger, 2022), and was lower for faces manipulated to appear infectious relative to those unmanipulated (e.g., van Leeuwen & Petersen, 2018;van Leeuwen & Jaeger, 2022). Hence, while results indicated that people are more motivated to avoid microbe-sharing contact with individuals possessing symptoms of current infection, they did not reveal evidence that people are motivated to avoid microbe-sharing contact with ethnic-outgroup members more than ethnic-ingroup members.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that participants (from a convenience sample including mostly undergraduates from an Australian university) reported similar levels of avoidance towards people with obesity as towards individuals with influenza 23 . Another study found that participants perceived individuals with acne-like facial blemishes as less healthy and that they would be less comfortable touching them compared with the same individuals without facial blemishes 112 . Arguably, the best evidence for behavioural avoidance of people with facial disfigurement comes from a study of responses to people with a port-wine stain 113 .…”
Section: The Smoke Detector Principlementioning
confidence: 99%
“…Indeed, the presence of pathogens does not always trigger the BIS, for instance in the case of a cooked hamburger infected by Escherichia coli bacteria. Instead, the BIS is sensitive to the probable presence of infectious cues in the environment and there are individual differences in the ability to detect pathogens and/or to avoid them (van Leeuwen & Jaeger, 2022 ). This, in turn, leads to individual differences in vulnerability to diseases (Duncan et al, 2009 ; Makhanova et al, 2022 ; Tybur et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“… 3 As commented by an anonymous reviewer, “discomfort ratings” are not by themselves direct measures of avoidance behaviors. We submit that discomfort ratings can serve as a reasonable proxy for the motivation to avoid contact with pathogens (see van Leeuwen and Jaeger ( 2022 ) and van Leeuwen & Petersen ( 2018 ) for other examples of the use of (dis)comfort ratings with physical contact to index pathogen avoidance). …”
mentioning
confidence: 99%